Network intrusion detection method based on improved FCM and rule parameter optimization in cloud environment - Chunqin ZANG; Lichun XIE (Dianxin kexue)
Aiming at the network intrusion detection problem in cloud environment,a method of network intrusion detection based on fuzzy inference was proposed.Firstly,it used the mutual information feature selection to reduce the feature of the sample.Then,the improved fuzzy C-means clustering method was used to cluster the training sample set,and the initial fuzzy rule base was got by the correspondence between each sample feature and cluster.After that,the refine parameter and consequent parameters of each rule were tuned to obtain an exact rule base.Finally,fuzzy inference was carried out on the input connection data based on the rule base,and it was classified to realize intrusion detection.Experimental results on the cloud intrusion detection dataset show that this method can detect the network intrusion accurately,and it is feasible and effective.